Different treatment regimens in breast cancer visceral crisis: A retrospective cohort study - Yang, Ruohan; Lu, Guanyu; Lv, Zheng; Jia, Lin; Cui, Jiuwei (Frontiers in Oncology, 2022)
Objective Breast cancer visceral crisis (VC) is caused by excessive tumor burden leading to severe organ dysfunction with poor prognosis. Traditional chemotherapy reduces the quality of life of patients without significantly improving survival. The aim of this study was to investigate the clinical characteristics of patients with VC and the prognosis by using different treatment options. Methods According to the 5th European School of Oncology (ESO)–European Society for Medical Oncology (ESMO) international consensus guidelines for advanced breast cancer guidelines (ABC 5), patients who were treated in the First Hospital of Jilin University from 2018 to 2022 and diagnosed with breast cancer VC were retrospectively analyzed. The analysis focused on the characteristics of the patients, the treatment regimens, and prognosis. Results A total of 133 patients were included in this study. As for metastasis breast cancer subtype, 92 (69.18%) were hormone receptor (HR) positive, human epidermal growth factor receptor 2 (HER-2) negative, 20 (15.04%) had HER-2 overexpression, and 21 (15.78%) were triple negative. All patients had an mOS of 11.2 months (range, 1.1–107.8 months). In different types of VC, the median overall survival (mOS) of bone marrow metastasis (BMM) was 18.0 months (range, 2.0–107.8 months), that of diffuse liver metastasis (DLM) was 8.1 months (range, 1.3–30.2 months), and that of meningeal metastasis (MM) was 9.0 months (range, 1.2–53.8 months). In 92 HR+, Her-2− patients using different treatment regimens, mOS was 6.2 months (range, 1.2–29.8 months) in the chemotherapy group while it was 24.3 months (range, 3.1–107.8 months) in the endocrine therapy (ET) group. Multivariate Cox regression analysis suggested that Eastern Cooperative Oncology Group (ECOG) scores and type of VC were associated with survival. Conclusion Prognosis varied in different types of VC. Patients with BMM had the best prognosis, and DLM had the worst. As treatment options continue to progress, our retrospective study showed a significant prolongation of overall survival (OS) in patients with VC compared to previous studies.